Bangladesh, a Middle Income Country by 2021 : What Will it Take in Terms of Poverty Reduction? - Gimenez, Lea; Jolliffe, Dean; Sharif, Iffath (World Bank, Washington, DC, 2014)
The vision 2021 plan and the associated perspective plan 2010-2021, adopted by the Government of Bangladesh lay out a series of development targets for 2021. Among the core targets identified to monitor the progress toward the vision 2021 objectives is that of attaining a poverty headcount of 14 percent by 2021. The purpose of this paper is to answer the following question: given Bangladesh's performance in poverty reduction over the last decades, can the author expect the proportion of the country's population living in poverty to be 14 percent by 2022? Using data from the last three household income and expenditures survey, we examine changes in poverty rates during 2000-2010, estimate net elasticity of poverty reduction to growth in per-capita expenditure, and then project poverty headcounts into the future. Our poverty projections based on the last three Household Income and Expenditure Surveys (HIES) surveys suggest that Bangladesh will achieve its Millennium Development Goal, or MDG goal of halving its poverty headcount to 28.5 percent by 2015 significantly ahead of schedule. Attaining the vision 2021 poverty target of 14 percent by 2021, however, is less certain as it requires a Gross Domestic Product, or GDP growth of at least 8 percent, or more than 2 percentage points higher than that observed in recent years.